1999
DOI: 10.1093/genetics/152.4.1487
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Wsc1 Protein, a Putative Receptor in the Stress Response of Saccharomyces cerevisiae

Abstract: Wsc1p, Wsc2p, Wsc3p, and Wsc4p, members of a novel protein family in the yeast Saccharomyces cerevisiae, are putative sensors or receptors in the stress response. Genetic characterization suggests that the WSC family are upstream regulators of the stress-activated PKC1-MAP kinase cascade and are required for the heat shock response and for maintenance of cell wall integrity. The Wsc proteins share sequence characteristics: at their N terminus they have a cysteine motif and a serine/threonine-rich domain predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(14 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…Wsc1 is among the best described mechano-sensors and coordinates mechano-transduction and cell wall integrity in budding yeast [48,[69][70][71]. This transmembrane protein accumulates predominantly at sites of polarized growth and functions as an upstream regulator of the Cell Wall Integrity pathway (CWI) that adjusts cell wall synthesis in response to chemical or heat stress [71][72][73]. Indeed, wsc1 cells are sensitive to cell wall damaging agents [72] and often lyse during polarized growth in processes such as budding and shmooing.…”
Section: A Conserved Family Of Mechano-sensors Containing Nano-spring...mentioning
confidence: 99%
“…Wsc1 is among the best described mechano-sensors and coordinates mechano-transduction and cell wall integrity in budding yeast [48,[69][70][71]. This transmembrane protein accumulates predominantly at sites of polarized growth and functions as an upstream regulator of the Cell Wall Integrity pathway (CWI) that adjusts cell wall synthesis in response to chemical or heat stress [71][72][73]. Indeed, wsc1 cells are sensitive to cell wall damaging agents [72] and often lyse during polarized growth in processes such as budding and shmooing.…”
Section: A Conserved Family Of Mechano-sensors Containing Nano-spring...mentioning
confidence: 99%
“…Our previous studies revealed that WSC family proteins act as methanol-sensing machinery for regulating methanol-induced gene expression in K. phaffii ( Ohsawa et al, 2017 ) . WSC family proteins were identified as “nanospring” mechanosensors of cell wall damage caused by high temperatures and hypo-osmotic stress in Saccharomyces cerevisiae (ScWsc1/ScSlg1) ( Lodder et al, 1999 ; Dupres et al, 2009 ). In the K. phaffii genome , three WSC family protein-encoding genes have been identified ( KpWSC1, KpWSC2 , and KpWSC3 ).…”
Section: Cell Wall Integrity and Stress Response Component Family Pro...mentioning
confidence: 99%
“…24 Deletions of WSC2, WSC3, and MTL1 lack strong phenotypes under most laboratory growth conditions and only slightly aggrevate those of a wsc1 and/or mid2 deletion in multiple combinations. 20,25 Therefore, the encoded sensors are thought to be less important and most studies have been directed towards Wsc1 sensor function.…”
Section: Ju¨rgen J Heinischmentioning
confidence: 99%
“…each of these regions is indispensable for activation of the CWI pathway upon extracellular stress. 20,25 The CRD displays significant similarity to a sequence from a fungal exoglucanase, which led to the hypothesis that it may interact with cell wall glucans. 9 Moreover, mutants with defects in O-mannosylation (pmt1 pmt3), which would cause a severe under-glycosylation of the STR sequences of all CWI sensors, also show cell lysis defects similar to wsc1 mid2 double deletions, which again are osmo-remedial.…”
Section: Ju¨rgen J Heinischmentioning
confidence: 99%